Effect of stress history on compressive and rheological behaviors of EPS geofoam. (20th December 2019) - Zou, Wei-lie; Wan, Liang-long; Han, Zhong; Wang, Xie-qun
Highlights: Precompression total strain mainly affects EPS' compressive properties. Precompression plastic strain mainly affects EPS' rheological properties. Short-term loads are helpful in attenuating the creep of EPS. Suggestions for using recycled EPS are provided. Abstract: This paper investigates the effect of stress history on the compressive and rheological behaviors of EPS geofoam. Short-time, constant-load and constant-strain precompression loadings were applied to impose different types of stress history on EPS samples. These samples were thereafter subjected to rapid compression, creep and stress relaxation tests to reveal their compressive (i.e. stress-strain relationship) and rheological (i.e. creep and stress relaxation) behaviors. Test results showed that (i) the yield strain of EPS increases as the maximum past strain level (precompression strain) increases and the stress-strain behavior of the EPS in the post-yielding range is not affected by its stress history; and (ii) the accumulated plastic strain during precompression decreases the rate of creep and stress relaxation. Based on the observed influence of stress history on the EPS, suggestions on the use of pre-loaded EPS were provided in this study.